CRYPTO ASSET REGULATION IN THE POST-REFORM ERA: A LITERATURE REVIEW ON THE HARMONISATION OF DIGITAL ECONOMY LAW, INVESTOR PROTECTION, AND THE TRANSFORMATION OF SHARIA FINTECH IN THE CONTEXT OF THE IMPLEMENTATION OF THE NEW CRIMINAL CODE AND THE PERSONAL DATA PROTECTION ACT FOR A SUSTAINABLE INDONESIAN CRYPTO MARKET - Irma Rachmawati Maruf; Mohd Syahrin (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2026)
The development of crypto assets in Indonesia in the post-reform era presents complex regulatory challenges regarding the harmonisation of digital economy law, investor protection, and the transformation of Sharia fintech. This study aims to comprehensively examine crypto asset regulation within the framework of the implementation of the new Criminal Code and the Personal Data Protection Act (PDPA) to create a sustainable Indonesian crypto market. The method employed is a literature review (library research) using a qualitative-descriptive analytical approach. The research findings indicate that regulatory fragmentation between Bappebti, OJK, and Bank Indonesia creates legal uncertainty that is detrimental to investors, whilst the implementation of the new Criminal Code and the Personal Data Protection Act presents an opportunity to strengthen protection through more comprehensive regulations on digital crime and personal data protection. The transformation of Sharia fintech offers a regulatory alternative that integrates Sharia principles with blockchain technology to create a fair, transparent, and inclusive crypto ecosystem. This study recommends integrated, adaptive, and value-based crypto regulations with synergy among stakeholders, effective oversight mechanisms, robust law enforcement, extensive investor education, and the integration of ESG principles for a sustainable Indonesian crypto market.